Roots of a region : Southern folk culture - Burrison, John A., 1942- (University Press of Mississippi, 2007)
Roots of a Region reveals the importance of folk traditions in shaping and expressing the American South. This overview covers the entire region and all forms of expression-oral, musical, customary, and material. --from publisher description.